Impact of Nitrogen Fertilizer Levels and Humic Acid Foliar Application on Durum Wheat Productivity in Libya - ادريس بلقاسم الشريف; شعيب محمد عمر; إدريس عمر المهدي (African Journal of Advanced Pure and Applied Sciences, 2025)
During winter season 2024/ 2025, a field experiment was conducted in Agricultural Research Station, Faculty of Agriculture (Suluq), Benghazi University, Libya to study different nitrogen fertilizer levels (75, 105 and 140 kg N/ ha) as main plot and two humic acid treatments (0 and 5 g/ L) as sub-plot on growth and productivity of durum wheat. Obtained results revealed that (140 kg N/ ha) produced the longest spikes (8.52 cm), highest number of grains/ spike and spikes/ m2 (66.82 and 418.62), respectively, heaviest 100 grain weight (5.25 g), highest grain yield (3.705 t/ ha) and harvest index (30.15 %), however, the highest plant height and biological yield resulted from 105 and 140 kg N/ ha. Sprayed plants with 5 g/ L humic acid were significantly increased all the studied traits. Humic acid application combined with 140 kg N/ ha produced the tallest spikes (9.02 cm), heaviest 100-grain weight (5.51 g), highest grain yield (4.830 t/ ha) and harvest index (35.49 %), however the highest number of spikes/ m2 resulted from both the mentioned treatment and (105 kg N/ ha) combined with humic acid spraying. The tallest plants, highest number of spikes/ m2 and biological yield resulted from any nitrogen level studied combined with humic acid application. From the aforementioned results, it can be concluded that treated durum wheat variety Kassi with 140 kgN/ ha with spraying (5g/L) humic acid significantly increase productivity under Suluq conditions.